Design considerations for a virtual reality-based nature therapy to release stress - Rozmi, M.D.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper presents the design and development of virtual reality-based nature therapy application as an alternative tool for stress relaxation. Forest therapy, a type nature therapy, supports healing of individuals through immersing oneself in the forest environments. Based on this concept, a simulation of a virtual reality forest therapy application is developed. According to the forest therapy, users will experience the therapeutic and relaxation effect of the forests when they immersed themselves in the forest atmosphere. For users to be fully immersed in the virtual forest environment and have similar experience to the actual forest therapy, design considerations in terms of the image realism, navigation methods and aids were discussed and highlighted. Essential nature elements such as types of forests, vegetation and natural habitat were suggested. The overall application design was presented in using a game concept. Positive results from users in a preliminary study indicate the potential of virtual reality as a tool in the field of therapy. Â© 2020 IEEE.